Evidence of a free-space ion acceleration layer in the plume of a quad confinement plasma source - Fabris,AL; Young,C; Knoll,A; Rosati,Azevedo E; Cappelli,M (Journal of Applied Physics, 2022)
The Quad Confinement Plasma Source is a novel plasma device developed for space propulsion applications, whose core is an E×Bdischarge with open electron drift. The magnetic field is produced by independently powered electromagnets able to generate different magnetic field topologies with the ultimate aim of manipulating the ion flow field for achieving thrust vectoring. In this work, we map the ion velocity in the plasmaejected from the Quad Confinement Thruster with different magnetic configurations using non-intrusive Laser-Induced Fluorescence diagnostics. Measurements show asteep ion acceleration layer located 8 cm downstream the exit plane of the discharge channel, detached from any physical boundary of the plasma source. In this location, the ion velocity increases from 3 km/s to 10 km/s within a 1 cm axial region. The ion acceleration profile has been haracterised under multiple testing conditions in order to identify the influence of the magnetic field intensity and topology on this peculiar ion acceleration layer.